Effect of Giving Black Cumin Seed (Nigella Sativa) Extract on Broiler Body Weight and Death Rate at Broiler Chicken Farming - Kusmiyati Kusmiyati; Nurrahmah Assyifa; I Wayan Merta; Dadi Setiadi (Jurnal Penelitian Pendidikan IPA, 2022)
This study aims to determine the effect of black cumin seed extract (Nigella sativa) on body weight and mortality of broiler chickens. Broiler chickens were randomly selected to represent 4 dose groups: control group (P0), 1.5 ml/liter extract (PI), 2 ml/liter extract (PII), and 2.5 ml/liter extract (PIII). The treatment was given by mixing black cumin seed extract (Nigella sativa) into the drinking water of broiler chickens for 3 weeks. The variables observed included body weight and mortality of broiler chickens. Data analysis used the one way ANOVA test followed by the LSD (Least Significant Difference) test. The results showed that the higher the dose of black cumin seed extract (Nigella sativa) given, the greater the broiler weight gain, while the mortality rate did not show any effect on the dose given. It can be concluded from this study that black cumin seed extract (Nigella sativa) has a significant effect on weight gain, but has no effect on broiler mortality